An exploratory study of smokers’ and stakeholders’ expectations of the implementation of a smoke-free policy in a university setting - Burns, Sharyn; Bowser, Nicole; Smith, J.; Jancey, Jonine; Crawford, Gemma (Australian Health Promotion Association, 2014)
Issues addressed: Smoke-free policies restricting tobacco use in public places are common in many middle- and high-income countries. Implementation of a smoke-free policy does not automatically result in a smoke-free environment, and appropriate enforcement procedures must be clearly communicated and implemented. Safety and restrictions in private spaces, especially student housing, are also issues that need to be explored. This research explored perceptions and attitudes of staff and student smokers and key stakeholders before the implementation of a complete campus ban on smoking at a large Australian university. Methods: Interviews were conducted with staff and student smokers (n = 9) and stakeholders (n = 9). The interviews explored attitudes towards a completely smoke-free policy in the university environment, perceptions relating to enforcement of and compliance with a completely smoke-free policy, and support needed from the university for smokers. Results: Participants generally supported a complete smoke-free policy. Key themes associated with the policy implementation included health implications, stigmatisation and labelling, liberty, and enforcement. Conclusion: Smoke-free policies require careful planning, evaluation, and appropriate enforcement to ensure maximum impact. Further research is needed to improve compliance with smoke-free policies in outdoor environments and diverse spaces. So what? A better understanding of attitudes and intentions towards a smoke-free policy before implementation may provide useful insight into the potential challenges and provide guidelines for the development of strategies to improve policy readiness and adherence. University support for smokers to quit is essential when implementing a smoke-free policy.